Pengaruh Layanan Informasi Karir terhadap Pemilihan Sekolah Lanjutan - Dika Lutfiana; Titin Swastinah; Sri Prawita (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2019)
The study was conducted at MTs.Nahdlatuth Thalabah Kesilir-Wuluhan 2017-2018 Academic Year with 33 respondents who were studied using the Population Research technique. This study uses the Product moment Correlation data analysis method. Data collection used is questionnaires. Based on the results of the study, the results obtained for career information services and the selection of advanced schools with r = 0.81269579, after consulting the product moment table, the r calculation is greater than r table, meaning that there is a relationship between electoral school. After consulting the price point r product moment for 33 significant levels of 5% 0.344 and 1% 0.442 it turns out that the statistical r value is higher than the table value, so the r calculation is greater than r table means the relationship. The hypothesis (Ha) says that there is an influence of career information services on the selection of high school students in class IXE MTs. Nahdlatuth Thalabah Kesilir - Wuluhan 2017-2018 Academic Year. Keywords: Career Information Services, Advanced School Selection